PLASTIK BIODEGRADABLE BERBAHAN AMPAS SINGKONG DAN POLIVINIL ASETAT - Nurul Asni; Djonaedi Saleh; Nadia Rahmawati (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Cassava waste by product from tapioca flour. For reducing environmental pollution cassava waste be use biodegradable plastics  by adding  polivinil asetat as  adhesive and glycerol as plastisizer. The aim  of this research is for  knowing  physical characteristic of biodegradable plastic.Ratio betwen cassava west and polivinil asetat (wt%) are 9:1; 8:2;7:3;6:4. Tensile  strength and elongation result from this research  for 6:4 ratio’s are 0,1019 ± 0,339 MPa  and  26,178%. Tensile strength and elongation for  9:1, ratio’s are 0,1659 ± 0,035 MPa and 22,386%.Key word : Cassava waste, Polivinil Asetat, Glycerol, Biodegradable plastics.